Organizational Culture Compensation And Spiritual Intelligence on Work Productivity - Kresensia Sulastri Astuti (Eduvest - Journal of Universal Studies, 2021)
This study aims to explain the relationship between organizational culture, compensation and spiritual intelligence on work productivity in the special area health office in Yogyakarta simultaneously and partially to work productivity in the special area health office in Yogyakarta. This research uses quantitative research methods. The research population sample shows that the Yogyakarta Special Region Health Service has 48 employees. The sample data collection technique is a probability sampling technique (saturated sampling) by taking a sample of 48 employees. The data collection method was using a questionnaire. The analysis technique used is simple regression with a significant level of 0.05. The results of this study indicate that (1) organizational culture has a positive effect on work productivity (2) compensation has a positive effect on work productivity (3) spiritual intelligence has a positive effect on work productivity (4) ) organizational culture, compensation, spiritual intelligence simultaneously influence work productivity.